Capital Market In Perspective Law Of Sharia Economy - Apik Anitasari Intan Saputri (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2019)
Economic activity is currently experiencing a very rapid development, starting from the development of the market in such a way, penetrating in the field of capital markets which become the traffic of the world economy, connecting between capital owners (investors) and entrepreneurs. Capital markets are a promising investment, entrepreneurs also began to take part in the world of Islamic capital markets which are currently dominated by Islamic countries in the world. With the development of these economic activities, the legislation is not only a rule, but is able to make the implementation of the law directed, protect and make all stakeholders in the world of capital markets have knowledge of the market and how to run it properly without any violations or criminal act in the Capital Market. Legal reform and regulation on the capital market must continue to be enforced. The development of the Islamic capital market in Indonesia is still relatively slow, as a result of the lack of level of knowledge and understanding of market participants and investors, the limited availability of information on the sharia capital market, lack of human resources (professionals) who are experts in the field of Islamic finance, institutional patterns and institutions in the framework of supervision is still considered a